The role of organizational resilience in social, economic, environmental and human sustainability: evidence form Chinese FMCG sector - Xu, Ming; Xu, Qiang; Wei, Sheng; Cong, Lei (Technological and Economic Development of Economy, 2024)
Despite the extensive research on sustainability dimensions, the researcher has not completely addressed all the dimensions of sustainability. Most of the times, sustainability is considered as a whole variable, however, the work on separate dimensions is lacking in the literature. Particularly, human sustainability is rarely addressed by the previous studies. Additionally, various dimensions of sustainability such as social, economic, environmental and human is rarely tested in relation to the organizational resilience. Therefore, to fill this gap, this study considered to examine the role of organizational resilience in social sustainability, economic sustainability, environmental sustainability and human sustainability in a sample of FMCG employees. The study used non-probability snowball sampling to collect data from managerial level employees. Data analysis is carried out by using SPSS. Findings identified that; organizational resilience has influential role in various dimensions of sustainability. The focus of the policymakers on organizational resilience can increase the socio-economic and environmental sustainability. The operational efficiency can strengthen the relationship between organizational resilience and sustainability. First published online 15 March 2024